COVID-19 and its psychological impact on working parents - Irshad, Seema; Begum, Nurjahan (Technium Social Sciences Journal, 2021)
Introduction: The control measures during COVID-19 taken by the Government such as curfew, lockdown, and social distancing had observed differences in controlling the spread of the disease around the Kingdom of Saudi Arabia which might contribute to psychological illnesses to working mothers. Methods: The present cross-sectional study experimentally investigated the psychological well-being of parents during the COVID-19 outbreak, by exploring parents' anxiety/depression, low social function and loss of confidence during pandemic, further examined that whether being female, married and working will effect on the mental status of the participants or not. Total number of participants (N=185) were assigned randomly in Saudi Arabia, 92 were males (49.73%) and 93 were females (50.27%). The 12-Item General Health Questionnaire (GHQ-12) (Goldberg & Williams, 1988), consists of 12 items were administered on the participants to find out their current mental status. Results: Result of the study revealed that females were high in poorer mental well-being, which in turn was associated with anxiety-depression, social dysfunction and lack of confidence due to their work being more heavily impacted by COVID-19 and the care burden at home. Discussion: Studies revealed that females were high in poorer mental well-being, which in turn was associated with anxiety-depression, social dysfunction and lack of confidence due to their work being more heavily impacted by COVID-19 and the care burden at home. Special supportive steps and measures should be implemented during and after the pandemic is over.